Glut-1 intensity and pattern of expression in thymic epithelial tumors are predictive of WHO subtypes - Thomas de Montpréville, Vincent; Marx, Alexander (Pathology, research and practice, 2015)
Objectives Glucose-transporter-1 (Glut-1) may be a useful marker for differentiating B3 thymomas and thymic carcinomas. Since the literature is limited, we undertook a study to evaluate its diagnostic value in a series of thymic epithelial tumors. Materials and methods Glut-1 expression was studied by the group of pathologists linked to the French national oncological network RYTHMIC. Immunostaining was performed on a whole section of one paraffin block in a series of 92 successive surgical specimens. Patterns (focal, zonal, diffuse) and intensity of Glut-1 expression were assessed and compared with WHO histological subtypes. Results Expression was mainly restricted to epithelial cells. Immature T-lymphocytes were negative. A diffuse, moderate or strong staining was observed in most thymic carcinomas (15/16). In B3 thymomas (10/11) and in B3 thymomas borderline to thymic carcinomas (5/6), a moderate to strong zonal staining was observed at distance from vessels and fibrous septa. This pattern sometimes created the aspect of an anastomosing network in large cellular lobules. In B1 thymomas, immunostaining highlighted foci of medullary differentiation (7/8). B2 thymomas (n = 25) were heterogeneous, with a spectrum of patterns ranging between those of B1 and B3 thymomas. Type A thymomas (n = 5) mostly presented a weak positivity but one aggressive case showed zonal moderate/strong positivity. Most AB thymomas (15/17) showed weak to moderate immunostaining in spindle cell areas. In micronodular thymomas (n = 3), epithelial cells and B-lymphocytes were weakly positive while follicular dendritic cells were strongly highlighted. One metaplastic thymoma displayed diffuse and moderate positivity. Conclusion Glut-1 expression globally depended on histological subtypes and the staining patterns (diffuse or zonal) were different between thymic carcinomas and type B3 thymomas. A comparative study of Glut-1 expression in atypical versus conventional type A thymomas appears warranted. Otherwise, restriction to epithelial cells makes likely a correlation with clinical assessment of glucose uptake in lymphocyte-poor tumors.